Case report: A collision tumor of clear cell renal cell carcinoma and clear cell papillary renal cell tumor - Lin, Yingsheng; Guo, Jinan; Li, Zaishang; Liu, Zengqin; Xie, Jing; Liu, Junxu; Jin, Hongtao; Xiao, Kefeng (Frontiers in Oncology, 2024)
We report the case of a 51-year-old woman who was initially hospitalized in the respiratory department with cough and fever. Urinary computed tomography (CT) showed two different incidental masses in the right kidney. The patient underwent a radical right nephrectomy without lymph node dissection and postoperative adjuvant treatment. The pathological examination of the surgical specimens showed a collision tumor composed of a clear cell renal cell carcinoma (CCRCC) and a clear cell papillary renal cell tumor (CCPRCT). To the best of our knowledge, this is the first such case reported to date. No recurrence of local or distant metastasis was found during routine follow-up 14 months after the operation.